Investigation of inoculum threshold and latent infection in Colletotrichum gloeosporiodes f. sp. manihotis in cassava cultivars - Fokunang, C.N.; Akem, C.; Ikotun, T.; Tembe-Fokunang, E.A.; Koona, P.; Dixon, A. (2000)
Studies were conducted at the advance pathology laboratory and glasshouse at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, to determine the inoculums threshold of fungal suspensions at different concentration levels, and also to investigate latent infection of cassava anthracnose disease pathogen, (colletotrichum gloeosporioides f. sp. Manihotis), in cassava cultivars. This study showed that fungal suspension could initiate disease infection at very low inoculums concentration of 3.3 x 10 colony forming units (CFU)/ml of sterile distilled water. There was a general increase in percentage leaf infection and defoliation in the cassava cultivars with increase in inoculums concentration and incubation period. Symptomless cassava plant materials after incubation at 25-2c for seven days showed the presence of acervuli of anthracnose fungus in more than 80% of the cassava cultivars. This was an indication that symptomless cassava materials contain C. gloeosporiodes f. sp. Manihotis that can only manifest itself under favourable environmental conditions during the course of growth and development of the host plant.